Pemanfaatan Sampah Organik Rumah Tangga Menjadi Eco-Enzyme Dalam Upaya Pemberdayaan Ekonomi Masyarakat Desa Rejasa - Trisna Puspita Sari; Ida Nyoman Basmantra (Vivabio: Jurnal Pengabdian Multidisiplin, 2023)
The 2023 National Education University's Community Service Program (KKN) activities are currently trying to increase productivity on a household scale. One of the productivity efforts being made is by empowering the economy of the Rejasa Village community by taking the opportunity to provide socialization to the community so they can process kitchen organic waste into Eco-Enzyme. Eco-Enzyme is the result of fermentation of organic waste in the form of vegetable residues and fruit peels. Eco-Enzyme has many benefits. One of them is as a disinfectant, liquid organic fertilizer, and others. Eco-Enzyme is an environmentally friendly product made from household waste that does not use chemicals. This fertilizer is suitable for development in Rejasa Village, Penebel because the raw material is easily available in gardens or agriculture and has high economic value. In addition, the technique of making Eco-Enzyme is very easy and can increase the productivity of the people of Rejasa Village. Therefore, the existence of socialization activities to empower the community through the manufacture of Eco-Enzyme can provide direct benefits in improving the economy as well as the quality of human resources regarding the importance of protecting the environment.   ABSTRAK Kegiatan-kegiatan KKN (Kuliah Kerja Nyata) Universitas Pendidikan Nasional 2023 saat ini berupaya meningkatkan produktivitas dalam skala rumah tangga. Salah satu upaya produktivitas yang dilakukan yaitu dengan pemberdayaan ekonomi masyarakat Desa Rejasa yaitu dengan mengambil peluang untuk memberikan sosialisasi masyarakat agar bisa mengolah sampah organic dapur menjadi Eco Enzyme. Eco Enzyme adalah hasil fermentasi sampah organic berupa sisa-sisa sayuran dan kulit buah. Eco Enzyme memiliki banyak manfaat. Salah satunya sebagai disinfektan, pupuk organic cair, dan lainnya. Eco Enzyme merupakan produk ramah lingkungan berbahan limbah rumah tangga yang tidak menggunakan bahan kimia. Pupuk ini cocok dikembangkan di Desa Rejasa, Penebel karena bahan bakunya mudah didapat di kebun ataupun pertanian dan bernilai ekonomi tinggi. Selain itu, Teknik membuat Eco Enzyme sangat mudah dan dapat meningkatkan produktivitas masyarakat Desa Rejasa. Oleh karena itu, adanya kegiatan sosialisasi untuk memberdayakan masyarakat melalui pembuatan Eco Enzyme dapat memberikan manfaat langsung dalam meningkatkan perekonomian sekaligus kualitas sumber daya manusia terhadap pentingnya menjaga lingkungan.